Revitalisasi Pendidikan Karakter melalui Dolanan Anak Guna Mewujudkan Generasi Sadar Budaya - Elvara Norma Aroyandini; Suwanto Suwanto; Nur Hamid (Faktor Jurnal Ilmiah Kependidikan, 2021)
This article aims to (1) explain the implementation of characters education through dolanan anak (traditional games for children) and (2) analyze the character values contained in dolanan anak. Type of this writing is an qualitative-descriptive explorative writing with the characteristic is pure research, to develop scientific or theoretical disciplines. The data source is the form of various relevant documents that were collected through the library research technique and analyzed using the content analysis model. Based on the discussion, it can be concluded that (1) Character education through dolanan anak can be carried out through various types of dolanan anak by internalizing the character values and (2) The values of character education in dolanan anak include honesty, responsibility, working together, discipline, creative, and hard working, where these values can be actualized in character education to create a culturally conscious generation.